Effects of a Web-Based Pediatric Oncology Legacy Intervention on the Coping of Children With Cancer. (January 2023) - Cho, Eunji; Dietrich, Mary S.; Friedman, Debra L.; Gilmer, Mary Jo; Gerhardt, Cynthia A.; Given, Barbara A.; Hendricks-Ferguson, Verna L.; Hinds, Pamela S.; Akard, Terrah Foster
Background: Recurrent or refractory cancer often results in substantial and extensive physical, emotional, psychosocial, and spiritual burdens for children and their families. However, the therapeutic benefits of legacy interventions in children with recurrent or refractory cancer have been examined only recently, with limited attention to specific effects on children's coping abilities. Objective: The purpose of this study was to determine the effects of a digital storytelling-legacy intervention on the adaptive coping of children with recurrent or refractory cancer. Methods: This study used a 2-arm randomized, waitlist-controlled trial design. A total of 150 children with recurrent or refractory cancer and their parents were recruited via Facebook advertisements. Results: The analysis sample included 92 dyads (35-intervention group, 57-control group). The legacy intervention showed small and statistically nonsignificant effects on primary-control and disengagement coping strategies among children with recurrent or refractory cancer. Conclusions: Legacy interventions using readily accessible digital storytelling have the potential to enhance the adaptive coping skills among children with recurrent or refractory cancer. Further research should determine how to enhance interventions tailored to this population to optimize the benefits.